Adult survival in migratory caribou is negatively associated with MHC functional diversity - Gagnon, Marianne; Yannic, Glenn; Boyer, Frédéric; Côté, Steeve D. (Heredity, 2021)
Genes of the major histocompatibility complex (MHC) are involved in acquired immunity in vertebrates. Only a few studies have investigated the fitness consequences of MHC gene diversity in wild populations. Here, we looked at the association between annual survival and body mass and MHC–DRB exon 2 (MHC–DRB) genetic diversity, obtained from high-throughput sequencing, in two declining migratory caribou (Rangifer tarandus) herds. To disentangle the potential direct and general effects of MHC–DRB genetic diversity, we compared different indices of diversity that were either based on DNA-sequence variation or on physicochemical divergence of the translated peptides, thereby covering a gradient of allelic-to-functional diversity. We found that (1) body mass was not related to MHC–DRB diversity or genotype, and (2) adult survival probability was negatively associated with point accepted mutation distance, a corrected distance that considers the likelihood of each amino acid substitution to be accepted by natural selection. In addition, we found no evidence of fluctuating selection over time on MHC–DRB diversity. We concluded that direct effects were involved in the negative relationship between MHC functional diversity and survival, although the mechanism underlying this result remains unclear. A possible explanation could be that individuals with higher MHC diversity suffer higher costs of immunity (immunopathology). Our results suggest that genetic diversity is not always beneficial even in genes that are likely to be strongly shaped by balancing selection.